1995
DOI: 10.1152/ajpheart.1995.269.4.h1363
|View full text |Cite
|
Sign up to set email alerts
|

Pressure wave propagation in a multibranched model of the human upper limb

Abstract: The influence of the large arteries and the peripheral load on pressure wave propagation in the human upper limb was investigated in an anatomically realistic multibranched model based on linear transmission theory. To mimic vascular changes seen in life, the viscoelastic properties of large arteries and the peripheral load properties (represented as modified windkessels) were altered as follows: Young's modulus (from 10.9 x 10(6) to 15.3 x 10(6) dyn/cm2) and phase (from 0 to 15 degrees) of the complex elastan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
57
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(62 citation statements)
references
References 0 publications
5
57
0
Order By: Relevance
“…26 These views were supported by noninvasive studies of central (carotid) and upper-limb pressure waves under different conditions 35 and by modeling studies. 18 Formal studies of transfer function between the ascending aorta and upper-limb arteries showed relative consistency, [12][13][14][15]25,36 including studies conducted with NTG used as a vasodilator agent. For the most part, these findings have been confirmed by others [13][14][15] who understandably had initially indicated strong skepticism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…26 These views were supported by noninvasive studies of central (carotid) and upper-limb pressure waves under different conditions 35 and by modeling studies. 18 Formal studies of transfer function between the ascending aorta and upper-limb arteries showed relative consistency, [12][13][14][15]25,36 including studies conducted with NTG used as a vasodilator agent. For the most part, these findings have been confirmed by others [13][14][15] who understandably had initially indicated strong skepticism.…”
Section: Discussionmentioning
confidence: 99%
“…6,11 The process involved convolution of the radial waveform by a generalized transfer function, which was taken to characterize pressure wave transformation in the upper limb. [12][13][14][15]18 The series of estimated aortic waveforms, together with the series of radial waveforms from which these were derived, were each ensemble-averaged over an 8-second period into a single calibrated waveform.…”
Section: Data Handling and Analysismentioning
confidence: 99%
“…The definite contour of the envelope waveform is composed of primary waves (generated by contraction of the left ventricle) and secondary reflected waves, which interfere with the primary ones. 13,14 Endothelial dysfunction may result in an increase in the tone of small arteries that would reduce oscillatory compliance. 15 Experimental data indicate that aging alters endotheliumdependent relaxation in arteries, 16 and loss of the oscillatory waveform represents an early and consistent finding with aging and hypertension.…”
Section: Michelson Et Al Fourier Analysis Of the Flow Velocity Envelopementioning
confidence: 99%
“…Recently, techniques based on the determination of a pressure transfer function between the radial artery and the aorta have been employed to provide an estimate of central pressure wave reflection. 8 In this issue of Hypertension, Millasseau et al 9 report on the accuracy of employing a generalized transfer function to the radial artery pressure pulse waveform to provide an estimate of the aortic augmentation index. The accuracy of the approach was assessed against data derived directly from the carotid pressure pulse waveform or after application of a transfer function to the waveform.…”
mentioning
confidence: 99%